Case report: Mohr-Tranebjaerg syndrome: hearing impairment as the onset of an insidious disorder with high recurrence risk - Eulalia Sousa; Maria Abreu; Nataliya Tkachenko; João Rocha; Cláudia Falcão Reis; Cláudia Falcão Reis; Cláudia Falcão Reis (Frontiers in Neurology, 2023)
Mohr-Tranebjaerg syndrome (MTS) is an X-linked recessive disorder caused by TIMM8A loss of function. It is characterized by sensorineural hearing loss in childhood, progressive optic atrophy in early adulthood, early onset dementia and psychiatric symptoms of variable expressivity. We present a family with 4 affected males, explore age-related and interfamilial variability and review the literature.Case reportA 31 years-old male developed psychiatric symptoms at age 18 and presented early onset dementia. Sensorineural hearing loss had been diagnosed in childhood. At 28yo, he developed dysarthria, dysphonia, dysmetria, limb hyperreflexia, dystonia, and spasticity following an acute encephalopathic crisis. WES revealed a hemizygous novel likely pathogenic variant in TIMM8A, c.45_61dup p.(His21Argfs*11), establishing the diagnosis of MTS. Genetic counseling of the family allowed the diagnosis of three other symptomatic relatives −3 nephews (11yo and two 6yo twins), children of a carrier sister. The oldest nephew had been followed since 4yo due to speech delay. Sensorineural hearing loss was diagnosed at 9yo, and hearing aids were prescribed. The two other nephews were monozygotic twins, and both had unilateral strabismus. One of the twins had macrocephaly and hypoplasia of the anterior temporal lobe, as disclosed by an MRI performed due to febrile seizures. Both had developmental delays, with the language being the most affected area. Their audiograms confirmed hearing loss. All three nephews were hemizygous for the familial TIMM8A variant.DiscussionHearing loss, an early sign of MTS due to auditory neuropathy, can often be overlooked until more severe features of the disorder manifest. Recurrence risk is high for female carriers, and reproductive options should be offered. Early monitoring of hearing and vision loss and neurological impairment in MTS patients is mandatory since early interventions may positively impact their development. This family showcases the importance of performing a timely etiological investigation of hearing loss and its impact on genetic counseling.